2015
DOI: 10.1007/s10147-015-0855-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical value of carbon nanoparticles as lymph node tracer in differentiated thyroid carcinoma requiring reoperation

Abstract: By tracing the thyroid and cervical regional lymph nodes with carbon nanoparticles, the parathyroid glands can be easily identified and protected to reduce the complications of transient hypoparathyroidism resulting from reoperation for residual or missed DTC. Carbon nanoparticle tracers also facilitate radical resection of lymph nodes at the central and lateral compartments of the neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…However, Zhu et al [26] reported a study on the effect of CN on central lymph node dissection and found that the number of cases of postoperative hypocalcemia in the CN group was significantly less than that in the control group ( P  = 0.013). Similar to other studies, [26,35] our study also found that CN could easily detect lymph nodes, and increased metastatic lymph nodes, and more lymph nodes were detected in the CN group than in the control group. Thus, CN might be used to achieve a more radical central neck dissection.…”
Section: Discussionsupporting
confidence: 91%
“…However, Zhu et al [26] reported a study on the effect of CN on central lymph node dissection and found that the number of cases of postoperative hypocalcemia in the CN group was significantly less than that in the control group ( P  = 0.013). Similar to other studies, [26,35] our study also found that CN could easily detect lymph nodes, and increased metastatic lymph nodes, and more lymph nodes were detected in the CN group than in the control group. Thus, CN might be used to achieve a more radical central neck dissection.…”
Section: Discussionsupporting
confidence: 91%
“…Further, the blood supply can remain unchanged, preventing excessive intraoperative episodes of bleeding within the operated area. Due to the application of carbon nanoparticles as a possible method of unequivocal identification of PGs, the risk of postoperative hypothyroidism is significantly reduced [93][94][95]. Finally, the application of carbon nanoparticles provides more accurate localization of lymph nodes for further dissection during thyroidectomy and better visualization of metastatic lymph nodes [92,[96][97][98][99][100].…”
Section: Carbon Nanoparticles In Parathyroid Glands Localizationmentioning
confidence: 99%
“…As a result, reoperation for thyroid cancer was also more and more performed. [ 8 ] Because of the destroyed anatomical structure and a large amount of fibrous and scar tissues in the surgical field for the previous surgery, reoperation was very difficult and the incidence of some complications, such as parathyroid gland (PG) damage and recurrent laryngeal nerve (RLN) injury, was increasing. [ 9 11 ] Therefore, some methods to identify the anatomical layers and structure were necessary to avoid more injury.…”
Section: Introductionmentioning
confidence: 99%